Gastric Cancer After Restrictive Bariatric Surgery: A Clinical Pitfall. (August 2014) - Scozzari, Gitana; Balmativola, Davide; Trapani, Renza; Toppino, Mauro; Morino, Mario
Although vertical banded gastroplasty is rarely performed at present, most bariatric surgery departments continue to follow up patients who underwent this procedure in the past few decades. In view of this, it is advisable for bariatric and general surgeons to know how to diagnose the very rare event of the development of a gastric cancer after this restrictive procedure. In this report, 2 cases of gastric cancer occurring years after vertical banded gastroplasty are presented, and clinical presentation and diagnostic difficulties are discussed.